2015
DOI: 10.1080/10942912.2015.1082138
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Composition and Antioxidant Activities of Tunisian Thymus capitatus L. Methanolic Extract

Abstract: Thymus capitatus has traditionally been considered as an anthelmintic, antispasmodic, carminative, emmenagogue, expectorant, rubefactient, sedative, stimulant, and tonic. This work was carried out to determine total polyphenol and total flavonoids, chemical composition of phenolics and to evaluate the antioxidant activities of the methanolic extract. Total phenolic contents were assayed using the Folin-Ciocalteu reagent, total flavonoid content was measured

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 23 publications
2
16
0
Order By: Relevance
“…They are extensively studied for their antioxidant, anticarcinogenic, and antimicrobial attributes. [23] We evaluated, in this study, the total phenolic and total flavonoid contents of A. rutifolia leaf extracts. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…They are extensively studied for their antioxidant, anticarcinogenic, and antimicrobial attributes. [23] We evaluated, in this study, the total phenolic and total flavonoid contents of A. rutifolia leaf extracts. The results are shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The TPC in our TcLME (73 mg GAE/g of DE = 8.18 mg GAE/g of DW) was significantly lower than the ones from the different bioclimatic zone (sub-humid, upper semi-arid, means semi-arid, lower semi-arid, upper arid and lower arid) in Tunisia with the values were ranged from 12.6 to 42.7 mg GAE/g of DW [60]. Using aerial parts of T. capitatus, Msaada et al [46] were found a lower amount of TPC in methanolic extract in four Tunisian regions, namely Kef, Grombelia, Bizerte, and Boukornine, with the values of 18. 40 To our knowledge, there has been no investigation on phenols contents of acetonic extract of T. capitatus, whereas TPC of EO was only reported in Morocco by Ouadan et al [61] using a mix of leaves and flowers, and the value (4.74 mg GAE/mL of EO) was close to the amount given in our TcLEO (5.18 mg GAE/mL of EO).…”
Section: Extraction Yield Total Phenolic and Total Flavonoid Contentsmentioning
confidence: 90%
“…Nowadays, EOs and their components are gaining increasing interest because of their relatively safe status and exploitation for potential multi-purpose functional uses [37]; they can be (nano) encapsulated with zein to increase the shelf life of food by inhibiting fungus [38]. T. capitatus possess different biological effects such as antioxidant, antifungal, antibacterial, and antiviral [39][40][41][42][43][44][45][46].…”
Section: Introductionmentioning
confidence: 99%
“…The phenolic content of plant extract depends on various parameters such as genetic and ecological factors, the part of the plant used, the extraction method employed and even plant age (Amarti et al 2010;Gharibi, Tabatabaei, & Saeidi, 2015). Msaada et al (2016), have revealed that both total phenols and flavonoids varied significantly among the region of collection, probably due to the dissimilarities in the soil, climate, solar lighting, humidity, and temperature, which could be affecting samples in each studied region.…”
Section: Phytochemical Screeningmentioning
confidence: 99%